Los notarios apostólicos en Santiago de Compostela a través de sus nombramientos - Ares Legaspi, Adrián (Scrineum, 2021)
The aim of this research is the analysis of one of the least studied type of notaries in Castille, the ones created by apostolic authority. In order to reach this purpose, we have based this research in the exam of five diplomas from the first half of the 16th century in which notaries are granted with the papal authority. We shall analyse the way this grant was developed, the skills required to these professionals, the functions and wrights they were given, the notarial signs they used or their writing practices, mainly the knowledge of languages and types of scripts.